QUALITY OF FINANCIAL STATEMENTS: THE IMPACT OF HUMAN RESOURCE QUALITY AND INTERNAL CONTROL SYSTEM - Maryunizah, Dewi; Delvi, Yulianda; Ahmad Munawar, Niknik (UIN Sunan Gunung Djati Bandung, 2025)
This research was conducted to determine the influence of the quality of human resources and internal control on the quality of Bandung City regional tax financial statements. The method used in this study is an associative descriptive method, with the data collection technique using a questionnaire as a research instrument; the statistical analysis method used in this study is multiple regression analysis. The primary data in this study was sourced from the Bandung City Regional Tax Revenue and Financial Management Office. The sample is the financial staff at the Bandung City Tax Finance Office, with as many as 50 respondents. Human Resources Quality significantly influences the Quality of Financial Statements. Internal Control Systems do not considerably affect the Quality of Financial Statements. The results of this study provide an overview to government agencies about the importance of improving the quality of human resources and the effectiveness of internal control to ensure better quality of financial reports. Thus, agencies can focus on developing employee competencies through training, certification, and relevant career development programs.